An experimental investigation on mechanical properties of calcined clay concrete embedded with bacillus subtilis. (2021) - Parashar, Arun Kumar; Gupta, Nakul; Kishore, Kamal; Nagar, Prince Akash
Abstract: This paper aimed at acquiring a new bacterial tool for increasing the strength and rehabilitation of micro-cracks management of calcined clay concrete. To achieve this phenomenon, Bacillus subtilis bacteria with the count of optimum density 10 8 CFU is embedded in the normal concrete along with the provision of calcined clay in the replacement of 10%, 15%, and 20% by weight of cement and cured for 7, 14, and 28 days. The specimens were targeted for testing in water absorption and compressive strength. The test result shows that the compressive strength of bacterial calcined clay concrete of the replacements of 10%, 15%, and 20% increased to 25%, 27%, and 28% respectively compared to nominal concrete at 28 days curing condition while the water absorption of the specimens was decreased in bacterial calcined clay concrete compared with calcined clay concrete. The overall study indicated that the bacteria demonstrated a helpful role in not only increase the strength of concrete but also helped in the self-healing of cracks.